LEARNING MODELS AT SD 72 ALUE NAGA BANDA ACEH - Citra Rifdah Zainiyah; Nurliah; Ahmad Hamzah; Siti Mayang sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses descriptive qualitative research methods, namelyresearch based on phenomena observed by researchers in accordance withevents that occurred at SD Negeri 72 Alue Naga Banda Aceh. Based on existingphenomena, research concludes that the learning models carried out by teachersat SD Negeri 72 Alue Naga Banda Aceh have all used learning models thatinclude the creation of new relationships, relationship dimensions, newknowledge, integrative thematics through content in class 4.5 , and 6. From theresults of research observations, it was found that SD Negeri 72 Banda Acehhas a special learning model in the learning process which influences thecharacter of the students. In this regard, teachers apply learning model strategiesin each high class according to the subject. which will be delivered. Studentactivities related to learning models can vary depending on the learning modelused. Some learning models commonly used in SD Negeri 72 schools includeinquiry, conceptual, problem-based learning, and project-based learningmodels. Student activities in these learning models can include searching andinvestigating things actively, working together in groups, developing newideas, being creative, thinking at a higher level, critically, practicing communication, sharing, being more open to socializing in the context ofproblem solving.